Targeted mutagenesis and functional analysis of adipokinetic hormone-encoding gene in Drosophila. (June 2015) - Sajwan, Suresh; Sidorov, Roman; Stašková, Tereza; Žaloudíková, Anna; Takasu, Yoko; Kodrík, Dalibor; Zurovec, Michal
Abstract: Adipokinetic hormones (Akhs) are small peptides (8–10 amino acid [aa] residues long) found in insects that regulate metabolic responses to stress by stimulating catabolic reactions and mobilizing energy stores. We employed Transcription activator-like effector nuclease (TALEN) mutagenesis and isolated an Akh 1 mutant carrying a small deletion in the gene that resulted in a truncated peptide; the second aa (Leu) was missing from the functional octapeptide. This null Dmel/Akh mutant is suitable to study Akh function without any effect on the C-terminal associated peptide encoded by the same gene. The mutant flies were fully viable and compared to the control flies, had significantly low levels of hemolymph saccharides including trehalose and were resistant to starvation. These characteristics are similar to those obtained from the flies carrying targeted ablation of Akh-expressing neurons (reported earlier). We also found that the Akh 1 mutants are slightly heavy and had a slow metabolic rate. Furthermore, we showed that the ectopic expression of Dmel∖Akh reverses the Akh 1 phenotype and restores the wild-type characteristics. Our results confirmed that Akh is an important regulator of metabolic homeostasis in Drosophila . Graphical abstract: Highlights: Drosophila Akh 1 mutant was generated by TALEN-mediated mutagenesis. The resulting mutant peptide has a leucine residue deleted at the second position. The Akh 1 mutants display low levels of free saccharides and resistance to starvation. The Akh 1 mutants also show slow metabolic rate and higher body mass. The ectopic expression of Akh restores wild-type characteristics.